2015
DOI: 10.1038/mi.2014.134
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-21 promotes intestinal IgA response to microbiota

Abstract: Commensal microbiota-specific Th17 cells are enriched in the intestines, which can convert into Tfh in Peyer’s patches, and are crucial for production of intestinal IgA against microbiota, however, the role of Th17 and Tfh cytokines in regulating the mucosal IgA response to enteric microbiota is still not completely known. In this study, we found that intestinal IgA was impaired in mice deficient in IL-17 or IL-21 signaling. IL-21, but not IL-17, is able to augment B cell differentiation to IgA+ cells as media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 43 publications
5
92
0
Order By: Relevance
“…IL-21 augments Th2 function and is important for B cell development (Cao et al, 2015;Ozaki et al, 2002Ozaki et al, , 2004Pesce et al, 2006). IL-21 is produced by Th17 cells and acts in an autocrine manner to boost Th17 differentiation (Korn et al, 2007;Nurieva et al, 2007).…”
Section: Il-21mentioning
confidence: 99%
“…IL-21 augments Th2 function and is important for B cell development (Cao et al, 2015;Ozaki et al, 2002Ozaki et al, , 2004Pesce et al, 2006). IL-21 is produced by Th17 cells and acts in an autocrine manner to boost Th17 differentiation (Korn et al, 2007;Nurieva et al, 2007).…”
Section: Il-21mentioning
confidence: 99%
“…B cells can undergo Ig class switch recombination (CSR) and acquire the ability to produce IgA after CD40-CD40L ligation in the presence of TGF- β with contribution from other cytokines including IL-4, IL-5, IL-6, IL-10, and IL-21 (58) (Figure 1). Other costimulatory signals such as B cell-activating factor of the TNF family (BAFF), a proliferation-inducing ligand (APRIL), retinoic acid (RA), and nitric oxide also facilitate CSR for the production of IgA (7, 9, 10).…”
Section: Iga and Secretory Igamentioning
confidence: 99%
“…Among these cells, follicular T helper (Tfh) cells (17) play a key role in both immunoglobulin CSR and somatic hypermutation in antigen recognizing regions and subsequent generation of high-affinity antibody producing plasma cells and memory B cells. The expression of CXCR5 by Tfh cells allow them to locate into B cell follicles, where they produce IL-21, an IgA promoting cytokine (5). Tfh were reported to differentiate from other Th cell subsets suggesting a plasticity of mucosal T cells and potential for rapid adaptation to the luminal environment and ultimately produce the mucosal IgA Abs needed to maintain homeostasis.…”
Section: Iga and Secretory Igamentioning
confidence: 99%
See 1 more Smart Citation
“…IL-21 can induce isotype class switch to IgA in CD40-stimulated human naive B cells; but this induction is inhibited by IL-4 (32). It was also reported that IL-21 can induce IgA isotype switching and also plasma cells homing to mucosal sites by synergistically interacting with transforming growth factor-β (TGFβ) suggesting that the impact of IL-21 on immunoglobulin production may be dependent on other interacting cytokines and a specific stage of B cell differentiation in vivo (18,33,34).…”
Section: Biological Effects Of Il-21 On Immune Cells B Cellsmentioning
confidence: 95%